Analysis of Traffic Accidents Regarding Traffic Participants in Recent Years in the Regions and Cities of the Republic of Uzbekistan - Khusanovich, Azizov Kudratilla; ugli, Kholikov Alisher Isan (European Journal of Life Safety and Stability (2660-9630), 2022)
In recent years, many people have died and been injured in road accidents in our country, as well as the moral and material damage caused by them. At the same time, their analysis plays an important role in the prevention and reduction of RTA. This article is devoted to the analysis of traffic accidents in the regions and cities of the country in 2015-2021.